Avaliação morfológica e nutricional de mudas pré-brotadas (MPB) de cana-de-açúcar cultivadas em diferentes substratos - Santi, Paulo Henrique Pizzi de (Universidade Federal de São Carlos, 2017)
The system of pre-sprouted seedlings is a new technology for sugarcane multiplication, which aims to develop materials with a high standard of uniformity and plant health. In this technique, the substrate plays an important role, as a means of supplying water, oxygen and nutrients, decisively influencing the quality of seedlings. The objective of this study was to evaluate the performance of substrates in the morphological and nutritional characteristics of pre-sprouted seedlings of sugarcane. Mini-stalks of the varieties RB92579, RB966928 and RB867515 were grown in sand, in sand + nutrient solution, and on three commercial substrates (S1, S2 and S3). The experimental design was completely randomized, in a 5x3 factorial scheme, with five replications. At 70 days after planting, height, stem diameter, shoot and root dry matter, Dickson's Quality Index, and use efficiency of nitrogen, phosphorus, and potassium were assessed. There was a significant interaction between substrates and sugarcane varieties for all variables studied, except for use efficiency of phosphorus and potassium, making it difficult to generalize about which substrate promoted the best development of pre-sprouted seedlings. The RB92579 variety of sugarcane showed the best efficiency in the use of N, P and K. The best efficiency in the use of P and K were obtained in substrates with greater restriction of nutrient supply, indicating that the mini-stalks is important reserve structure in the seedling production phase. The dry root mass was the most suitable parameter to evaluate the quality of pre-sprouted sugarcane seedlings.
Morphological and nutritional evaluation of sugarcane pre-sprouted seedlings grown on different substrates
Keywords: Saccharum officinarum; Biometria; Meio de cultivo; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::FERTILIDADE DO SOLO E ADUBACAO